Encoding Heteronormativity in the Target Culture: Slovenian Translations of The Merchant of Venice - Gorjanc, Vojko (Meta, 2012)
This article discusses how linguistic and translation norms, as evident in dictionaries, enforce the ideology of heteronormativity in Slovenia. The aim of this paper is to show how translation norms concerning homoeroticism were shaped in the translation of classical literature in Slovenia in the twentieth century. Translation norms are shaped in a certain period of time and in a certain environment among translators and others involved in translation according to social and cultural circumstances, expectations, and adaptations of topics to these expectations, in which the translation contrasts the initial norms with the norms of the target culture. At the same time, the linguistic norms of the standard language are created as a result of speakers’ continuous adaptation to a social and cultural environment, as a result of adapting to the current social ideal. It is assumed that translations contributed to creating a model of heteronormativity, which continues to characterize the Slovenian community today because of the limited number of new translations of classical works of literature. The paper concludes with a brief analysis of evidence of homosexuality in Slovenian translations of Shakespeare’s The Merchant of Venice.